-1
$\begingroup$

First of all, I'd like to apologize for this question because I'm sure the answer is simple, I'm just a bit rusty on basic algebra skills after being out of practice for so long. I can't seem to work out what's happening on line 4 of this example:

Image of example here

\begin{align*} x={}&\frac{y}{1-3y}+2 \\ \implies\hspace{1.8cm} x-2={}&\frac{y}{1-3y} \\ \implies(x-2)(1-3y)={}&y \\ \implies-3(x-2)y-y={}&2-x \\ \implies\hspace{2.6cm} y={}&\frac{2-x}{5-3x} \\ \implies\hspace{1.7cm} h^{-1}(x)={}&\frac{2-x}{5-3x}=\frac{x-2}{3x-5}. \end{align*}

I can see some factorization has been done, but I really can't grok the whole thing. Is anyone willing to explain it?

$\endgroup$
3
$\begingroup$

The writer went a little fast and skipped a step

$$(x-2)(1-3y)=y$$ $$(x-2)-3(x-2)y=y$$ $$-3(x-2)y-y=-(x-2)$$


Alternatively,

$$x=\frac y{1-3y}+2.$$

Multiply by $1-3y$

$$x(1-3y)=x-3xy=y+2(1-3y)=2-5y.$$

Move all $y$ terms to the right

$$x-2=3xy-5y.$$

Divide by $3x-5$, $$y=\frac{x-2}{3x-5}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.